Ion‐Directed Coordinative Polymerization of Copper(II) Pyridyl‐Alcohol Complexes Through Thiane Functionalities. Issue 4 (15th January 2019) - Schmitz, Sebastian; Izarova, Natalya V.; Besson, Claire; van Leusen, Jan; Kögerler, Paul; Monakhov, Kirill Yu.
Abstract : A mononuclear complex [Cu(HL· S)2 (NO3 )2 ] (1 ) and a one‐ dimensional coordination polymer [Cu(HL· S)Cl2 ] n (2 ) [HL· S = 4‐(pyridin‐2‐ylmethyl)tetrahydro‐2 H ‐thiopyran‐4‐ol] showcase the structure‐directing role of the counterions in their formation reaction: monodentate ligation of NO3 – and Cl – induces an octahedral (with two HL· S per Cu in1 ) or trigonal‐bipyramidal (with one HL· S per Cu in2 ) Cu II coordination environment. In contrast to1 exhibiting no coordinative metal–sulfur bonds in the crystal lattice (space group P 21 / c ), 2 ( P 21 / c ) features intermolecular Cu–S contacts of 2.3188(7) Å. The coordination compounds are thermally stable up to ca. 160 °C. Whereas1 demonstrates the spin‐like behavior of an isolated central Cu II ion, compound2 exhibits weak antiferromagnetic intra‐chain coupling with J ≈ –2.1 cm –1 between neighboring Cu II ions. Abstract :